2016
DOI: 10.1161/strokeaha.115.011674
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Thrombolysis in Patients Dependent on the Daily Help of Others Before Stroke

Abstract: Background and Purpose-We compared outcome and complications in patients with stroke treated with intravenous thrombolysis (IVT) who could not live alone without help of another person before stroke (dependent patients) versus independent ones. Methods-In a multicenter IVT-register-based cohort study, we compared previously dependent (prestroke modified Rankin Scale score, 3-5) versus independent (prestroke modified Rankin Scale score, 0-2) patients. Outcome measures were poor 3-month outcome (not reaching at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 20 publications
9
63
1
1
Order By: Relevance
“…[16][17][18][19] Local study investigators completed the forms using prospectively ascertained in-hospital IVT registries. Completed forms from all centers were compiled in the coordinating center in Amsterdam, where data were pooled and analyzed as described previously.…”
Section: Methods Study Population Procedures and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] Local study investigators completed the forms using prospectively ascertained in-hospital IVT registries. Completed forms from all centers were compiled in the coordinating center in Amsterdam, where data were pooled and analyzed as described previously.…”
Section: Methods Study Population Procedures and Outcomesmentioning
confidence: 99%
“…mRS scores were obtained by the local center through a telephone interview or by outpatient clinic visit with the patient or caregiver, as described in previous research. [16][17][18][19] Safety measures were symptomatic intracranial hemorrhage and mortality at 3 months. Symptomatic intracranial hemorrhage was defined according to the criteria of the European Cooperative Acute Stroke Study II: any hemorrhage with neurological deterioration, indicated by a National Institute of Health Stroke Scale score ≥4 than the value at baseline or the lowest value within 7 days, or any hemorrhage leading to death.…”
Section: Methods Study Population Procedures and Outcomesmentioning
confidence: 99%
“…The ThRombolysis in Ischaemic Stroke Patients (TRISP) study is a collaboration of 12 European stroke centres and comprises a cohort of over 10 000 consecutive patients treated with IVT 1. We used data of patients treated up to 31 December 2014 (see online supplementary appendix file 1).…”
Section: Methodsmentioning
confidence: 99%
“…In the UK national stroke audit, pre-stroke mRS is one of the core descriptors collected (11). In practice, decisions on treatment are often based on premorbid function (12). …”
Section: Introductionmentioning
confidence: 99%